Multilocus phylogenetic and geospatial analyses illuminate diversification patterns and the biogeographic history of Malagasy endemic plated lizards (Gerrhosauridae: Zonosaurinae). (26th February 2015) - Blair, C.; Noonan, B. P.; Brown, J. L.; Raselimanana, A. P.; Vences, M.; Yoder, A. D.
Abstract Although numerous studies have attempted to find single unifying mechanisms for generating Madagascar's unique flora and fauna, little consensus has been reached regarding the relative importance of climatic, geologic and ecological processes as catalysts of diversification of the region's unique biota. Rather, recent work has shown that both biological and physical drivers of diversification are best analysed in a case‐by‐case setting with attention focused on the ecological and life‐history requirements of the specific phylogenetic lineage under investigation. Here, we utilize a comprehensive analytical approach to examine evolutionary drivers and elucidate the biogeographic history of Malagasy plated lizards (Zonosaurinae). Data from three genes are combined with fossil information to construct time‐calibrated species trees for zonosaurines and their African relatives, which are used to test alternative diversification hypotheses. Methods are utilized for explicitly incorporating phylogenetic uncertainty into downstream analyses. Species distribution models are created for 14 of 19 currently recognized species, which are then used to estimate spatial patterns of species richness and endemicity. Spatially explicit analyses are employed to correlate patterns of diversity with both topographic heterogeneity and climatic stability through geologic time. We then use inferred geographic ranges to estimate the biogeographic history of zonosaurines within each of Madagascar's major biomes. Results suggest constant Neogene and Quaternary speciation with divergence from the African most recent common ancestor ~30 million years ago when oceanic currents and African rivers facilitated dispersal. Spatial patterns of diversity appear concentrated along coastal regions of northern and southern Madagascar. We find no relationship between either topographic heterogeneity or climatic stability and patterns of diversity. Ancestral state reconstructions suggest that western dry forests were important centres of origin with recent invasion into spiny and rain forest. These data highlight the power of combining multilocus phylogenetic and spatially explicit analyses for testing alternative diversification hypotheses within Madagascar's unique biota and more generally, particularly as applied to phylogenetically and biologically constrained systems.